Intergenerational Transmission of Risk Attitudes: A Revealed Preference Approach - Andrea Leuermann; Sarah Necker (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This study investigates whether the willingness to take income risks revealed by occupational choice is transmitted from parents to their children. Using data from the German Socio-Economic Panel (SOEP), we find that fathers' riskiness of job is a significant determinant of children's occupational risk, in particular sons' (excluding parent-child pairs with identical occupations). This is the first piece of evidence for intergenerational transmission of risk attitudes relying on real world behavior. It shows that not only individuals' own assessments of their risk attitudes correlate (found by previous studies) but also risk preferences shown in exactly the same situation.
Keywords: D12; D81; J24; 330; Risk preferences; intergenerational transmission; occupational choice; Risikopräferenz; Generationengerechtigkeit; Offenbarte Präferenzen; Deutschland